2022
DOI: 10.1523/jneurosci.2200-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

APPsα Rescues Tau-Induced Synaptic Pathology

Abstract: Alzheimer's disease (AD) is histopathologically characterized by Ab plaques and the accumulation of hyperphosphorylated Tau species, the latter also constituting key hallmarks of primary tauopathies. Whereas Ab is produced by amyloidogenic APP processing, APP processing along the competing nonamyloidogenic pathway results in the secretion of neurotrophic and synaptotrophic APPsa. Recently, we demonstrated that APPsa has therapeutic effects in transgenic AD model mice and rescues Ab-dependent impairments.Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Bace-1 and Adam10) that results in fragments with distinct functions in regulating neural circuits (Jimenez et al, 2011; Nunan and Small, 2000; Vassar et al, 1999). While Aβ-fragments were mostly linked to pathological conditions (Opazo et al, 2018), neuroprotective and synaptic plasticity enhancing properties have been attributed to soluble APPα (Bold et al, 2022; Fol et al, 2016; Jimenez et al, 2011; Mockett et al, 2017; Richter et al, 2018; Tan et al, 2018). Moreover, recent advances demonstrated that APP and its fragments are regulators of homeostatic synaptic plasticity which aims at keeping neuronal activity in a dynamic range through synaptic adaptations (Galanis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Bace-1 and Adam10) that results in fragments with distinct functions in regulating neural circuits (Jimenez et al, 2011; Nunan and Small, 2000; Vassar et al, 1999). While Aβ-fragments were mostly linked to pathological conditions (Opazo et al, 2018), neuroprotective and synaptic plasticity enhancing properties have been attributed to soluble APPα (Bold et al, 2022; Fol et al, 2016; Jimenez et al, 2011; Mockett et al, 2017; Richter et al, 2018; Tan et al, 2018). Moreover, recent advances demonstrated that APP and its fragments are regulators of homeostatic synaptic plasticity which aims at keeping neuronal activity in a dynamic range through synaptic adaptations (Galanis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the highly plastic nature of synapses, synaptic dysfunction and synapse loss are reversible processes even in the presence of established pathology, which is highly relevant when treating symptomatic patients. Importantly, the rescue of spine density by APPsα is not limited to THY-Tau22 mice, as we recently showed similar spine density restoring properties of APPsα also in Tau transgenic P301S mice ( Bold et al, 2022 ). Moreover, APPsα also normalized spine density under conditions of Aβ plaque pathology ( Fol et al, 2016 ) and in gene targeted mice lacking endogenous APP and APLP2 ( Richter et al, 2018 ), indicating a more general function for synaptic repair.…”
Section: Discussionmentioning
confidence: 70%
“…Sarkosyl-insoluble and sarkosyl-soluble Tau aggregates were separated as described previously (Eckermann et al, 2007;Bold et al, 2022). For the Tau fractionation, mice were sacrificed by cervical 10.3389/fncel.2023.1106176 dislocation 3 months post-injection at 12 months of age and the brain was rapidly removed.…”
Section: Protein Extraction Based On Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…App, the second protein in the aforementioned list, has also been shown to regulate synaptic maintenance or drive synaptic loss. Two recent studies are particularly relevant in this regard: The first study ( Bold et al, 2022 ) showed that APPsα (the proteolytic cleavage product of APP along the nonamyloidogenic pathway, i.e., the one not producing Aβ) rescued abnormally low spine density in tauopathy model mice, even when applied at nanomolar concentrations. In contrast, the second study ( Lee et al, 2022 ) as well as many others, showed that soluble forms of oligomeric Aβ (the proteolytic APP cleavage product along the amyloidogenic pathway) drove excitatory synapse loss.…”
Section: Discussionmentioning
confidence: 99%